Gray Value Evaluation of Mandibular Bone in the Adult and Elderly: Pilot Study for Osteoporosis Screening - Inka Saraswati; Cindy Lorenza; Bramma Kiswanjaya; Syurri I Syahraini (Wolters Kluwer Medknow Publications, 2023)
Introduction: Postmenopausal women are more at risk of osteoporosis than men of the same age. Osteoporosis is often undetected due to lack of symptoms. The aim of the study was to explore the potential of gray value (GV) in clinical panoramic radiographs as a screening method for osteoporosis. Cross-sectional comparative study using secondary data. GV of mandible in panoramic radiographs between male and female of several age groups were compared. X-ray parameters were considered. Materials and Methods: A total of 294 panoramic radiographs were obtained from regular clinical activity regardless of mA (3.3-8 mA), and divided into sexes and ages 31 to 45, 46 to 60, and 61 to 75 years old. A subset of 60 panoramic radiographs obtained by a narrow range of mA (5.7-6.4 mA) were randomly selected and then divided into sexes and ages 32 to 53 and 54 to 75 years old. Average GV was recorded. Average GV between age groups (divided by sexes) was evaluated by one-way analysis of variance (ANOVA) for groups with unrestricted mA, and unpaired t-test for restricted mA. Results: Average GV without mA restriction were not significantly different between age groups in men (P = 0.883) and women (P = 0.617). If mA is restricted, average GV was significantly different between age groups in women (P = 0.007) but were not significantly different between age groups in men (P = 0.386). Conclusion: GV obtained from panoramic radiographs may have potential in detecting osteoporosis if x-ray parameters are kept in narrow range. It would not have the same screening potential if the range of x-ray parameters are too wide.